A clinical perspective towards oropharyngeal dysphagia management in neurological conditions: a brief literature review - Tosun, Samet; Karalı, Fenise Selin; Çınar, Nilgün (The European Research Journal, 2025)
Dysphagia is a condition affecting the passage of solid and liquid food into the stomach due to impaired swallowing mechanisms caused by neurological factors like stroke, progressive diseases, and brain injury. Symptoms usually manifest within seconds of swallowing. In this brief review, the clinical perspective towards oropharyngeal dysphagia management from a speech and language therapist’s point of view in neurological conditions will be outlined. This review was carried out by a brief literature screening. This review includes swallowing performance assessment and oropharyngeal dysphagia therapy techniques. Instrumental evaluation techiques were typically used to determine dysphagia presence in the clinical settings. Based on the findings of instrumental evaluation, clinicians must decide the therapy plan. In dysphagia, treatments contain behavioral interventions, central nervous system stimulation, and postural techniques. Behavioral therapy approaches include maneuvers, swallowing exercises, and postural techniques. Electrical stimulation approaches, such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), improve the brain’s ability to change and adapt, known as neural plasticity. In conlusion, the significance of evidence-based treatment in swallowing therapies is essential to enhance the comprehension of dysphagia therapy efficacy, particularly through randomized controlled trials.